Pengaruh Pembatasan pakan terhadap performa ayam pedaging strain yang berbeda - Lantowa, Z.; Londok, J.J.M.R.; Imbar, M.R. (ZOOTEC, 2021)
THE EFFECT OF FEED RESTRICTION ON THE PERFORMANCE OF BROILERWITH DIFFERENT STRAINS. This study aims to measure the growth performance of broilers with different strains through a feed restriction pattern at the beginning of growth (starter). This study used 72 day-old broilers consisting of 36 Cobb strains and 36 Lohman strains selected from each of them. -each 100 heads to get almost the same body weight obtained successively from PT. Charoen Phokphand and PT. Japfa Comfeed Indonesia. The design used was a completely randomized design (CRD) with a 2x4 factorial pattern with 3 replications. The A factor is the difference in strains (A1 = Lohman, A2 = Cobb), while the B factor is the time of feed restriction (B0 = no feed restriction, B1 = feed restriction starts on day 8, B2 = Feed restriction starts on day 11, B3 = Feed restriction begins On day 14. There were 8 treatment combinations. Feed restriction was carried out as much as 20 percent. The measured variables were feed consumption, body weight gain, and feed conversion. The results of the analysis of variance showed that there was a significant interaction (P <0.05) between the strains different from the start of the feed restriction on feed consumption and body weight gain, while the feed conversion variable did not show a significant interaction (P> 0.05) .Tukey's test results showed that the feed consumption in the combination of Lohman strain treatment with limitation time of 11 days (98.95) is not significantly different (P> 0.05) with the combination of A1B0 (97.52), A2B3 (91.34), but A2B0 (95.36) is significantly different (P <0.05) is higher with all combinations treatment. The results of the analysis of variance showed that there was a significant interaction (P <0.05) between factor A and factor B. The results of the Tukey test showed that the treatment of A1B2 (54.63) was not significantly different (P> 0.05) with A1B1 (51, 70), thus with treatment A2B0 (48.13), treatment A1B0 (49.93) with A2B1 (49.13), A2B3 (49.12), A2B0 (48.13) and A2B2 (47.21) . Lohman strain broiler and 20% restriction with restriction time starting on the eleventh day gave the best performance response.Â Keywords: Strain, feed restriction, time limitation